Mathematical modelling of wood drying process - Raimondas Čiegis; Vadimas Starikovičius; Audrius Volkas (Lietuvos Matematikos Rinkinys)
This work discusses issues on the design of finite difference schemes for modelling the moisture movement process in the wood. A new finite difference scheme is proposed. The stability and convergence in the maximum norm are proved.